Daily Associations of Stress and Eating in Mother–Child Dyads. (June 2017) - Dunton, Genevieve F.; Dzubur, Eldin; Huh, Jimi; Belcher, Britni R.; Maher, Jaclyn P.; O'Connor, Sydney; Margolin, Gayla
Background and Aims. This study used Ecological Momentary Assessment (EMA) in mother–child dyads to examine the day-level associations of stress and eating. Method. Mothers and their 8- to 12-year-old children ( N = 167 dyads) completed between three (weekday) and eight (weekend) EMA survey prompts per day at random nonschool times across 8 days. EMA measured perceived stress, and past 2-hour healthy (i.e., fruit and vegetables) and unhealthy (e.g., pastries/sweets, soda/energy drinks) eating. Results. Children reported more healthy and unhealthy eating on days when their mothers also engaged in more healthy and unhealthy eating, respectively. On days when mothers' perceived stress was greater than usual, they reported more healthy eating. Discussion and Conclusions. Eating behaviors were coupled between mothers and children at the day level. Mothers' stress was related to their own eating but not to children's eating.